Effect of nitrogen and sulphur fertilization on the quality of barley protein - Y. Dostálová; L. Hřivna; B. Kotková; I. Burešová; M. Janečková; V. Šottníková (Plant, Soil and Environment, 2015)
A small-plot field experiment was set up during 2011, 2012 and 2013 to test the effect of nitrogen (N) fertilizers and nitrogen fertilizers combined with sulphur (S) in the nutrition of spring barley cv. Bojos. The following parameters were studied, the effect of fertilization on grain yield, specific weight, percentage of the grain retained on a 2.8 mm and 2.5 mm sieve, the content of starch and proteins, and the percentage of protein fractions. Also the influence of weather conditions on the studied parameters was evaluated. Starch content and specific weight of grain were not influenced by the fertilizer applied. Grain yield was rising until the overall dosage reached 50 kg N/ha and 21 kg S/ha while any higher rate of fertilizer reduced the yield. The percentage of A- and B-hordeins increased and the content of C- and D-hordeins reduced as the fertilizer rate increased. A significant effect of weather on the monitored parameters as well as on the percentage of protein fractions was demonstrated. The results enabled a conclusion that there is no improvement in technological quality of barley grain once the optimal rate of fertilizer has been reached. The optimal rate is influenced by weather conditions during the growing season.